Real‐world clinical applicability of pathogenicity predictors assessed on SERPINA1 mutations in alpha‐1‐antitrypsin deficiency. Issue 9 (28th June 2018) - Giacopuzzi, Edoardo; Laffranchi, Mattia; Berardelli, Romina; Ravasio, Viola; Ferrarotti, Ilaria; Gooptu, Bibek; Borsani, Giuseppe; Fra, Annamaria
Abstract: The growth of publicly available data informing upon genetic variations, mechanisms of disease, and disease subphenotypes offers great potential for personalized medicine. Computational approaches are likely required to assess a large number of novel genetic variants. However, the integration of genetic, structural, and pathophysiological data still represents a challenge for computational predictions and their clinical use. We addressed these issues for alpha‐1‐antitrypsin deficiency, a disease mediated by mutations in the SERPINA1 gene encoding alpha‐1‐antitrypsin. We compiled a comprehensive database of SERPINA1 coding mutations and assigned them apparent pathological relevance based upon available data. "Benign" and "pathogenic" variations were used to assess performance of 31 pathogenicity predictors. Well‐performing algorithms clustered the subset of variants known to be severely pathogenic with high scores. Eight new mutations identified in the ExAC database and achieving high scores were selected for characterization in cell models and showed secretory deficiency and polymer formation, supporting the predictive power of our computational approach. The behavior of the pathogenic new variants and consistent outliers were rationalized by considering the protein structural context and residue conservation. These findings highlight the potential of computational methods to provide meaningful predictions of the pathogenic significance of novel mutations and identify areas for further investigation. Abstract : The growth of publicly available data informing upon genetic variations offers great potential for personalised medicine. We assessed performance of known pathogenicity predictors using SERPINA1 mutations causing α1‐antitrypsin deficiency as a model. New mutations identified in the ExAC database and predicted as pathogenic by the best performing algorithms were characterised in cellular models. Our results overall support the potential of computational methods to provide meaningful predictions for novel mutations and identify areas for further investigation.